Potential Planning for Micro Hydro Power Plants (PLTMH) by Utilizing River Flows in Kab. Gayo Lues - Arnawan Hasibuan; Kasman; Herman Fithra; Alpaslan DURMUŞ; Rizky Almunadiansyah; Widyana Verawaty Siregar (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The abstract should be clear, concise, descriptive and should provide a brief introduction to the problem. A statement: Electricity is a necessity that plays an important role in human life. So, the potential plan for Persada Tongra village is to build an environmentally friendly power plant that includes renewable energy. Terangun district, Gayo Lues Regency, has the potential of a river that can be used as a micro-hydro power plant (PLTMH) source. The purpose of this research is to find out how big the potential of water to generate electrical energy is in the river in Persada Tongra Village. The method used in calculating the water discharge in the river flow uses the floating method, and measurements are made using a stopwatch. Based on the measurement results at the location, it produces water potential with a maximum discharge of 1.16 m3/s, a total height of 1.47 m, and the highest generated power is 16.71 kW. It is hoped that the results of this study can later be used as an energy source where this energy source can be used to generate electricity in the Gayo Lues district.